Nowcasting the impact of COVID-19 on education, intergenerational mobility and earnings inequality in Sub-Saharan Africa - Guido Neidhöfer; Nora Lustig; Patricio Larroulet (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Using microsimulations, we nowcast the impact of learning losses caused by COVID-19 on secondary school completion rates, intergenerational mobility of education, and long-run earnings inequality in eight countries Sub-Saharan Africa. On average, secondary school completion rates decrease by 12 percentage points overall and by 16 points for children with low-educated parents. Interestingly, in most countries the gender gap diminishes because for men the projected decrease in secondary school completion is higher. However, a small additional impact on girls' education due to the Covid-19 induced rise in teenage pregnancy is observed in some countries. Intergenerational mobility of education decreases from 1 to close to 50 percent, depending on the country. As a result of the heterogeneous reduction in average years of schooling for advantaged vs. disadvantaged children, earnings inequality could increase between one and four Gini points, depending on the assumptions.
Keywords: I24; I38; J62; 330; COVID-19; lockdowns; human capital; school closures; intergenerational persistence; education; inequality; Africa